1969
DOI: 10.1159/000179727
|View full text |Cite
|
Sign up to set email alerts
|

Micropuncture Study of the Action of Angiotensin-II on Tubular Sodium and Water Reabsorption in the Rat

Abstract: The effect of val-äangiotensin-II-amide on tubular sodium and water reabsorption in the rat kidney was studied by micropuncture techniques. An angiotensin infusion of 0.2–0.5 µg/min/kg caused a significant increase ( + 16 mEq/l) in the sodium concentration of tubular fluid collected from the distal tubule, as compared to collections made from the same site of the tubule during saline infusion alone. TF/P-inulin ratio remained unchanged. Glomerular filtration rate, sodium and water excretion were unaltered. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

1970
1970
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 12 publications
5
24
0
Order By: Relevance
“…In some previous reports (22) The observations that the decrease in proximal tubule SFP or SNGFR at maximal perfusion rate was diminished support the concept that the sensitivity of the feedback mechanism is attenuated by CEI administration. Increases in volume delivery rates in the range of those observed for normal conditions (10)(11)(12)(13)(14)(15) nl/min) resulted in less change in SFP and SNGFR during infusion of CEI. Thus, the slight but significant renal vasodilation observed after administration of CEI can be explained on the basis of a decreased sensitivity of the feedback mechanism, allowing less than expected vascular resistance for the given higher distal tubule volume flow rate.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…In some previous reports (22) The observations that the decrease in proximal tubule SFP or SNGFR at maximal perfusion rate was diminished support the concept that the sensitivity of the feedback mechanism is attenuated by CEI administration. Increases in volume delivery rates in the range of those observed for normal conditions (10)(11)(12)(13)(14)(15) nl/min) resulted in less change in SFP and SNGFR during infusion of CEI. Thus, the slight but significant renal vasodilation observed after administration of CEI can be explained on the basis of a decreased sensitivity of the feedback mechanism, allowing less than expected vascular resistance for the given higher distal tubule volume flow rate.…”
Section: Resultsmentioning
confidence: 79%
“…The possible influence of the renin-angiotensin system on the base-line control setting of renal hemodynamics has received somewhat greater support (3,8,9). Other reports have suggested that angiotensin might also be one important determinant of renal tubular absorptive function (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Since an increased filtration fraction favors proximal tubular volume reabsorption via peritubular mechanisms, a direct effect of All on proximal function could not be ascertained by these studies. Though several micropuncture studies utilizing systemic All administration found no effect on proximal volume reabsorption (8)(9)(10), other studies applying All directly to the peritubular surface found a biphasic dose response. Steven (1 1) found inhibition of proximal volume reabsorption when 2 X 10-8 M All was infused into superficial peritubular capillaries.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have proposed models in which angiotensin II (AII) is a critical mediator for the control of glomerular filtration rate (1), renal autoregulation (2), and tubular sodium reabsorption (3,4). It is not clear whether the AII postulated to mediate these control mechanisms is produced within the kidney or reaches the kidney from the systemic circulation.…”
Section: Introductionmentioning
confidence: 99%